Modified hydrotalcite and paint remover containing same
By combining modified hydrotalcite and polyaspartic acid, a paint remover without halogenated hydrocarbon solvents is prepared, which solves the existing problems of low paint removal efficiency and poor environmental protection of EMU car bodies, and achieves It achieves an efficient, environmentally friendly and low-cost paint removal effect.
Patent Information
- Application Number
- CN202411422534.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-17
AI Technical Summary
When the paint is removed on the EMU, most of the prior art rely on physical methods or chemical methods containing organic solvents, which have problems such as low efficiency, poor environmental protection, and complex operation.
It is prepared by using modified hydrotalcite through hydrothermal reaction and modified with polyaspartic acid to form a paint remover without halogenated hydrocarbon solvents. The paint remover is biodegradable and has strong penetration, decomposition, Stripping ability.
It achieves the rapid and complete removal of various types of coatings without the need for toxic solvents and heating, and is less corrosive to the aluminum alloy surface. It is easy to operate, environmentally friendly and efficient.
Smart Images

Figure CN119320575A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of chemistry and coatings, and particularly relates to a modified hydrotalcite and application thereof in a paint stripper. The invention also relates to an environmentally friendly and efficient hydrotalcite gel paint stripper containing the modified hydrotalcite. Background Art
[0002] EMUs are the main type of passenger trains in my country, and they have been in operation since the beginning of this century. As time goes by, the surface coating of EMUs has gradually reached the end of its service life and must be repaired or even repainted. The body of ordinary passenger trains is made of carbon steel, and the surface paint film is mostly removed by physical methods such as sandblasting. However, this method is not suitable for EMU bodies made of aluminum alloy sheets. Therefore, at present, manual grinding can only be used to remove the paint on site, which is time-consuming, labor-intensive and inefficient.
[0003] Compared with physical paint stripping, the use of paint strippers to remove the paint film by chemical methods is undoubtedly more suitable for EMU bodies. Early paint strippers generally used organic solvents such as dichloromethane and N-methylpyrrolidone. With the development of the times, the use of dichloromethane and N-methylpyrrolidone has gradually been prohibited by laws and regulations. Therefore, alternative products that do not contain halogenated alkanes and N-methylpyrrolidone have appeared in the prior art. For example, the Chinese invention patent application "Paint stripper composition and preparation method thereof" with publication number CN117859121A (publication date April 9, 2024) discloses a paint stripper composition containing tetrahydrofuran, amines and an organic solvent selected from hydrocarbons, alcohols, and alcohol ethers. For example, the Chinese invention patent application "A paint stripper, paint stripping method and application thereof" with publication number CN117701058A (publication date March 15, 2024) discloses a paint stripper comprising 3-10 parts of an ester compound, 0.3-1.5 parts of an emulsifier, and 88-97 parts of water. The paint stripping method comprises soaking the parts to be stripped in the paint stripper for 10-40 minutes, polishing for 20-40 minutes after the soaking, and then cleaning. In addition, the Chinese invention patent application "A water-based paint stripper and its preparation method" with publication number CN118085631A (publication date May 28, 2024) discloses a water-based paint stripper composed of 50.0-60.0% of a main solvent, 10.0-40.0% of a co-solvent, 1.0-2.0% of a thickener, 1.0-3.0% of a surfactant, 0.5-1.0% of a sedimentation agent, and 3.0-4.0% of a promoter; wherein the main solvent is one or two of benzyl alcohol, benzaldehyde, N-methyl-2-pyrrolidone, benzoic acid, or isohexanediol, the co-solvent is at least one of 2-methyl-2,4-pentanediol, ethanolamine, propylene glycol or water, and the surfactant is one or two of sodium polymethacrylate, nonylphenol polyoxyethylene ether, polystyrene sulfonic acid or 3-hydroxypropane sulfonic acid; the workpiece to be stripped needs to be immersed in a paint stripper at 60°C.
[0004] The paint strippers of the prior art still contain organic solvents, or need to be heated during paint stripping, and need to be polished after paint stripping. Therefore, considering factors such as environmental protection, safety, paint stripping efficiency and product cost, it is necessary to develop an environmentally friendly, efficient, low-cost and easy-to-operate paint stripper.
[0005] Layered Double Hydroxides (LDHs) are a new type of inorganic functional material with a layered structure, and its interlayer ions are exchangeable. Polyaspartic acid-modified hydrotalcite compounds are mostly used to treat heavy metal pollution. For example, the Chinese invention patent application "A polyaspartic acid intercalated hydrotalcite composite material and its preparation method and application" with publication number CN110624513A (publication date December 31, 2019) discloses a polyaspartic acid intercalated hydrotalcite composite material for adsorbing lead ions in water, which is prepared by hydrothermal reaction of magnesium nitrate, aluminum nitrate, sodium hydroxide and polyaspartic acid. However, the application of hydrotalcite compounds (LDHs) in paint strippers has not been seen so far. Summary of the invention
[0006] In view of the above technical problems, the present invention provides a novel modified hydrotalcite and a paint stripper containing the modified hydrotalcite. The paint stripper of the present invention does not contain halogenated hydrocarbon solvents, is biodegradable, and has minimal harm to humans and the environment. The paint stripper has strong penetration, decomposition, and stripping capabilities, can quickly and thoroughly remove various types of coatings, and has low corrosiveness to the surface of aluminum alloys. In addition, the paint stripper of the present invention is easy to use, only needs to be soaked for a certain period of time and then washed with water, and the construction operation is convenient.
[0007] In order to achieve the above technical effects, the present invention adopts the following technical solutions:
[0008] A modified hydrotalcite is prepared by the following steps:
[0009] I. Using Zn(NO3)26H2O, A1(NO3)39H2O and hexamethylenetetramethyltetramine (HMT) as raw materials, hydrotalcite with an average particle size of 2.0 to 3.0 μm was obtained by hydrothermal reaction;
[0010] II. The hydrotalcite obtained in step I is added to a Tris-HCl-NaCl buffer solution of polyaspartic acid, ultrasonically dispersed for 10 to 30 minutes, and then magnetically stirred for 20 to 60 minutes; liquid-solid separation, the obtained solid is rinsed with distilled water at least 3 times, and dried to obtain;
[0011] The mass ratio of polyaspartic acid to the hydrotalcite is 1:5-20.
[0012] Preferably, in step I, the molar ratio of Zn(NO3)26H2O, Al(NO3)39H2O and hexamethylenetetramethyltetramine is:
[0013] Zn(NO3)26H2O∶A1(NO3)39H2O∶hexamethylenetetramethyltetramine=2:1~1.5:4.
[0014] Preferably, in step I, the hydrothermal reaction temperature is 130-180° C., and the reaction time is 10-18 hours.
[0015] As a preferred embodiment, the hydrotalcite is prepared by the following steps:
[0016] I-1. Add Zn(NO3)26H2O and A1(NO3)39H2O to water at 50-70°C to a concentration of 0.05-0.15 mol / L of zinc nitrate; then add hexamethylenetetramethyltetramine and stir thoroughly to dissolve; wherein the molar ratio of Zn(NO3)26H2O, A1(NO3)39H2O and hexamethylenetetramethyltetramine is:
[0017] Zn(NO3)26H2O∶A1(NO3)39H2O∶hexamethylenetetramethyltetramine=2:1:4;
[0018] I-2. The mixed solution obtained in step I-1 was transferred to a hydrothermal reactor, heated to 130 to 180 ° C, kept for 10 to 18 hours, and cooled to room temperature;
[0019] I-3. The reaction system obtained in step I-2 is centrifuged, and the precipitate is washed with water at least 3 times, 30 to 50 ml each time; then washed with 98% ethanol at least 3 times, 30 to 50 ml each time; dried at 60 to 70 ° C for 8 to 12 hours, ground into a fine powder, and passed through a 120 to 150 mesh sieve to obtain.
[0020] Preferably, in step I-1, the concentration of zinc nitrate is 0.1 mol / L.
[0021] Preferably, in step I-2, the temperature of the hydrothermal reaction is 140-160° C., more preferably 150° C.; the hydrothermal reaction time is 12-16 h, more preferably 14 h.
[0022] Also preferably, in the step I-2, the hydrothermal reaction kettle can be transferred to a heating device to be heated for hydrothermal reaction.
[0023] More preferably, the heating device is an oven.
[0024] Preferably, in step I-3, the drying temperature is 65° C. and the drying time is 10 h.
[0025] Also preferably, in step I-3, drying is carried out in a forced air drying oven.
[0026] Preferably, in step II, the concentration of polyaspartic acid in Tris-HCl-NaCl buffer is 1 mg / ml.
[0027] Preferably, the Tris-HCl-NaCl buffer is prepared by the following method:
[0028] Take Tris base and NaCl and dissolve them in distilled water to make the concentration of Tris base 0.6-0.7 mol / L, and adjust the pH value to 8.5-9 with dilute hydrochloric acid to obtain the product; wherein the molar ratio of Tris base to NaCl is 1:3.
[0029] Preferably, in step II, the ultrasonic dispersion time is 15 to 25 minutes, more preferably 20 minutes.
[0030] Preferably, in step II, the magnetic stirring time is 25 to 35 min, more preferably 30 min.
[0031] Also preferably, in step II, the drying is vacuum drying, the drying temperature is 50 to 70° C., and the drying time is 12 to 24 hours.
[0032] The present invention also provides a composition, comprising the modified hydrotalcite, and also comprising a main solvent, D-limonene, dimethyl succinate, triethanolamine, a surfactant, biological glue, benzotriazole and water; based on the total mass of the composition, the mass percentage of each component is:
[0033] The modified hydrotalcite comprises 0.5-2%, the main solvent comprises 30-40%, D-limonene comprises 5-10%, dimethyl succinate comprises 5-10%, triethanolamine comprises 4-8%, a surfactant comprises 0.05-0.5%, biological glue comprises 1-5%, benzotriazole comprises 0.1-1%, and the balance comprises water;
[0034] Wherein, the main solvent is selected from one or more of ethylene glycol monoethyl ether, benzyl alcohol, cyclohexanol and heptanol in any proportion;
[0035] The surfactant includes a nonionic surfactant and an anionic surfactant.
[0036] Preferably, the mass percentages of the components of the composition are:
[0037] The modified hydrotalcite comprises 0.6-1.6%, the main solvent comprises 30-38%, D-limonene comprises 5-9%, dimethyl succinate comprises 5-8%, triethanolamine comprises 4-8%, surfactant comprises 0.2-0.45%, biological glue comprises 1-3%, benzotriazole comprises 0.1-1%, and the balance comprises water.
[0038] More preferably, the mass percentages of the components of the composition are:
[0039] The modified hydrotalcite comprises 1-1.5%, the main solvent comprises 35-37%, D-limonene comprises 6-7%, dimethyl succinate comprises 6-7%, triethanolamine comprises 5-6%, surfactant comprises 0.2-0.35%, biological glue comprises 1.5-2%, benzotriazole comprises 0.5-0.7%, and the balance comprises water.
[0040] Preferably, the nonionic surfactant is selected from one or more of alkylphenol polyoxyethylene ether (wherein the value of n is greater than 8), alkylolamide and alkyl glycoside.
[0041] Preferably, the anionic surfactant is sodium dodecylbenzene sulfonate.
[0042] Preferably, the mass ratio of the nonionic surfactant to the anionic surfactant is 1:1 to 3:1.
[0043] Preferably, the bio-gum is selected from one or more of tri-gum, xanthan gum and guar gum in any proportion.
[0044] Another object of the present invention is to provide a paint stripper using the above composition as a raw material.
[0045] In addition, the present invention also provides a method for preparing the paint stripper, comprising the following steps:
[0046] A. Prepare the components according to the ratio;
[0047] B. The main solvent and D-limonene are mixed uniformly in a container, and triethanolamine, a surfactant and the modified hydrotalcite are added and mixed uniformly to obtain a mixed solution A for standby use;
[0048] C. Mix water, dimethyl succinate, bio-glue and benzotriazole in a container to obtain a mixed solution B for later use;
[0049] D. Mix the mixed solution A obtained in step B and the mixed solution B obtained in step C, and stir them evenly to obtain the product.
[0050] Another object of the present invention is to provide the use of the above paint stripper or the paint stripper prepared by the above method in paint layer removal, especially in the removal of paint layer coated on the surface of EMU body.
[0051] The present invention also provides a paint stripping process, comprising using the paint stripping agent or the paint stripping agent obtained by the above preparation method, comprising the following steps:
[0052] The paint stripper of the present invention or the paint stripper obtained by the above preparation method is directly applied on the paint surface to be stripped, left to stand for 40 minutes to 1 hour, then the bulging paint film is peeled off, the paint stripping residue is cleaned, and the paint stripper is rinsed with water.
[0053] Preferably, the paint surface to be removed includes the paint layer applied on the surface of the EMU train body.
[0054] The modified hydrotalcite of the present invention plays the role of corrosion inhibitor in the paint stripper composition and can be fully adsorbed on the metal surface, thereby protecting the aluminum alloy body of the EMU.
[0055] In this specification, unless otherwise specified, the "water" refers to purified distilled water or deionized water.
[0056] The paint stripper of the invention does not contain any toxic or harmful components and is friendly to the environment and operators.
[0057] The paint stripper composition of the present invention has moderate consistency and good sag property, and can be retained for a long enough time even on a vertical and smooth surface of a motor vehicle body, thereby ensuring that the paint stripping active ingredients can play a role.
[0058] The paint stripper composition of the present invention has high paint stripping efficiency, does not require heating during paint stripping, does not require polishing after paint stripping, is easy to operate, saves time and labor, and is low-carbon and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] The present invention is further described below in conjunction with the accompanying drawings.
[0060] Figure 1 The photo shows the corrosion inhibition effect of the modified hydrotalcite of the present invention on metals.
[0061] A: Aluminum test piece after being polished and cleaned with 200-grit sandpaper;
[0062] B: Aluminum test piece after being immersed in 2% NaOH solution for 4 hours;
[0063] C: Aluminum test piece after being immersed in 2% NaOH+modified hydrotalcite solution of Example 1 for 4 hours.
[0064] Figure 2 The photographs show the painted panels prepared in the application examples.
[0065] Figure 3 The photo shows Figure 2 The paint panel shown was painted with the paint stripper of Example 5. After standing for 50 minutes, the paint film had bubbled and was peeled off. DETAILED DESCRIPTION
[0066] The present invention is described below with reference to specific examples. It will be appreciated by those skilled in the art that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention in any way.
[0067] The experimental methods in the following examples are conventional methods unless otherwise specified. The raw materials, reagents, etc. used in the following examples are commercially available products unless otherwise specified.
[0068] Research Example 1 Study on the process conditions for preparing hydrotalcite by hydrothermal method
[0069] Hydrotalcite must have a suitable particle size and uniform particles to facilitate the loading of polyaspartic acid. When preparing hydrotalcite by hydrothermal method, reaction temperature and time are important parameters affecting particle size and uniformity. The following experiment was conducted to investigate the effects of these two parameters on the average particle size and particle uniformity of hydrotalcite.
[0070] 1. Investigation of hydrothermal reaction time
[0071] I-1. Add Zn(NO3)26H2O (2.4 g, 0.008 mol) and A1(NO3)39H2O (1.5 g, 0.004 mol) to 80 ml of distilled water at 60 ° C, then add hexamethylenetetramine (2.24 g, 0.016 mol) and stir thoroughly to dissolve;
[0072] I-2. The mixed solution obtained in step I-1 was transferred to a hydrothermal reactor, and then the hydrothermal reactor was transferred to an oven, and the reaction was carried out at 150 ° C for the time shown in Table 1, and the heating was stopped and cooled to room temperature;
[0073] I-3. The reaction system obtained in step I-2 was centrifuged, and the precipitate was washed with distilled water 3 times, 50 ml each time, and then washed with 98% ethanol 3 times, 50 ml each time; dried by forced air at 65°C for 10 hours, ground into fine powder, passed through a 120-mesh sieve, measured the average particle size of the fine powder, and observed the particle uniformity under a microscope. The results are shown in Table 1.
[0074] Table 1 Results of hydrothermal reaction time for hydrotalcite synthesis
[0075] Reaction time 7h 14h 21h Average particle size 0.7μm 2.5μm 3.8μm Particle uniformity Uniform Uniform Uneven
[0076] The results in Table 1 show that at 150° C., the reaction time is preferably about 14 h; if the reaction time is too short, the obtained hydrotalcite particle size is too small; if the reaction time is too long, the hydrotalcite particles are uneven.
[0077] 2. Investigation of hydrothermal reaction temperature
[0078] According to the reaction steps in the previous section, hydrotalcite was prepared with the same raw materials, except that the hydrothermal reaction time was 14 h, and the reaction was performed at the temperature shown in Table 2 for 14 h, centrifuged, washed, and dried to obtain hydrotalcite, and the average particle size of the fine powder was measured to detect its uniformity. The results are shown in Table 2.
[0079] Table 2 Results of hydrothermal reaction temperature investigation for hydrotalcite synthesis
[0080] Reaction temperature 80℃ 150℃ 210℃ Average particle size 0.3μm 2.3μm 4.5μm Particle uniformity Uniform Uniform Uneven
[0081] The results in Table 2 show that when the reaction time is 14 hours, the reaction temperature is preferably about 150°C; if the reaction temperature is too low, the hydrotalcite particle size is too small; if the reaction time is too long, the hydrotalcite particle size increases, it is easy to stick together, and the uniformity is poor.
[0082] 3. Conclusion
[0083] Through experiments, it is preferred that the hydrothermal reaction temperature of hydrotalcite is about 150°C and the reaction time is about 14 hours.
[0084] Example 1 Preparation of a modified hydrotalcite
[0085] According to the hydrothermal reaction conditions optimized in Research Example 1, hydrotalcite was prepared. The specific operation was as follows:
[0086] I-1. Zn(NO3)26H2O (2.4 g, 0.008 mol) and A1(NO3)39H2O (1.5 g, 0.004 mol) were added to 80 ml of distilled water at 60°C, followed by hexamethylenetetramine (2.24 g, 0.016 mol), and stirred thoroughly to dissolve;
[0087] I-2. The mixed solution obtained in step I-1 was transferred to a hydrothermal reactor, and then the hydrothermal reactor was transferred to an oven, reacted at 150 ° C for 140h, the heating was stopped, and cooled to room temperature;
[0088] I-3. The reaction system obtained in step I-2 was centrifuged, and the precipitate was washed 3 times with distilled water, 50 ml of distilled water each time, and then washed 3 times with 98% ethanol, 50 ml of ethanol each time; dried under 65°C with air drying for 10 h, ground into a fine powder, and passed through a 150-mesh sieve to obtain hydrotalcite (LDH).
[0089] Then, polyaspartic acid was loaded according to the following steps to obtain modified hydrotalcite:
[0090] II-1. Take Tris base (30 g, about 0.13 mol) and sodium chloride (22.8 g, about 0.39 mol) and dissolve them in 200 ml of distilled water, adjust the pH value to 8.5 with dilute hydrochloric acid to obtain a Tris-HCl-NaCl buffer solution for later use;
[0091] II-2. Take 100 mg of polyaspartic acid, dissolve it in 100 ml of Tris-HCl-NaCl (pH = 8.5) buffer prepared in step II-1, and add 1 g of hydrotalcite (LDH) prepared in step I-3, uniformly disperse it by ultrasonication for 20 minutes, and stir it magnetically for 30 minutes. Centrifuge, rinse the precipitate with water 3 times, then transfer it to a vacuum oven, dry it at 60°C overnight under vacuum conditions, and grind it in an agate mortar after natural cooling to obtain modified hydrotalcite (LDH / PASP) loaded with polyaspartic acid.
[0092] Test Example 1 Corrosion inhibition effect of the modified hydrotalcite of the present invention on metals
[0093] Take 2 portions of 2% NaOH solution, each 100 ml; add 1 g of LDH / PASP prepared according to the method described in Example 1 to obtain a test solution. 2 aluminum test pieces were polished with 200-grit sandpaper, washed with water and acetone once, and dried (see Figure 1 A); then put them into two test solutions respectively, let them stand for 4 hours, take them out, and observe the surface of the test pieces. Figure 1 B and C. Among them, Figure 1 Figure B shows that after the aluminum specimen was immersed in 2% NaOH solution for 4 hours, obvious corrosion spots were visible on the surface; Figure 1 FIG. C shows that after the aluminum test piece is immersed in a 2% NaOH solution to which the modified hydrotalcite (LDH / PASP) of the present invention is added for 4 hours, there is no corrosion spot on the surface, and there is no obvious difference compared with the aluminum test piece shown in FIG. A.
[0094] Therefore, the modified hydrotalcite loaded with polyaspartic acid (LDH / PASP) of the present invention has a good corrosion inhibition effect on metal aluminum in an alkaline system and can protect metal aluminum from corrosion.
[0095] Example 2-5 A composition and a paint stripper prepared therefrom
[0096] The compositions of Examples 2-5 are shown in Table 3 (in Table 3, the total percentage of each component is 100%).
[0097] The paint stripper is prepared by the following steps:
[0098] A. Prepare the components according to the ratio;
[0099] B. The main solvent and D-limonene are mixed uniformly in a container, and triethanolamine, a surfactant and the modified hydrotalcite are added and mixed uniformly to obtain a mixed solution A for standby use;
[0100] C. Mix water, dimethyl succinate, bio-glue and benzotriazole in a container to obtain a mixed solution B for later use;
[0101] D. Mix the mixed solution A obtained in step B and the mixed solution B obtained in step C, and stir them evenly to obtain the product.
[0102] Comparative Example 1-3 A composition and a paint stripper prepared therefrom
[0103] The compositions of Comparative Examples 1-3 are shown in Table 3 (in Table 3, the total percentage of each component is 100%).
[0104] The paint stripper of the comparative example was prepared according to the same steps as in Example 2.
[0105] Test Example 1 Performance Determination of Paint Strippers of Examples 2-5 and Comparative Examples 1-3
[0106] 1.Consistency:
[0107] The consistency of the paint stripper should not be too thick (not spreading on the surface) nor too thin (too fluid and unable to fully contact the surface). According to the provisions of MH / T 6074-1080, the paint stripper should flow 18cm to 23cm within 5 minutes. In this way, the paint stripper can be attached to the smooth and flat coating by brushing, flowing or spraying, and can adhere to the vertical EMU coating surface for a sufficient time. The results are shown in Table 4.
[0108] 2. Full immersion corrosion:
[0109] The test is carried out in accordance with the provisions of MH / T 6074-1080. The paint stripper should not cause the mass change per unit area of the test plate to exceed 0.3 mg / cm per 24 hours. 2 The results are shown in Table 4.
[0110] 3. Paint stripping efficiency
[0111] According to HG / T2881-1997, the percentage of the expansion and wrinkling area of the paint film was checked at the specified time. The results are shown in Table 4.
[0112] Table 3 Composition of paint stripper compositions of Examples 2-5 and Comparative Examples 1-3
[0113]
[0114] a: prepared according to the method of Example 1.
[0115] Table 4 Paint stripper performance test results of each embodiment and comparative example
[0116] Test samples Flow distance / cm <![CDATA[Mass change mg / cm 2 > Paint stripping efficiency % Example 2 15 1.8 76 Example 3 32 1.4 83 Example 4 12 0.9 85 Example 5 23 0.2 95 Comparative Example 1 8 2.5 56 Comparative Example 2 46 1.3 65 Comparative Example 3 9 2.6 52
[0117] Application Example Application of the paint stripper of Example 5
[0118] Self-made painted board: Tinplate is used as the base plate, and epoxy primer, polyurethane intermediate paint, and weather-resistant acrylic polyurethane topcoat are sprayed on it in sequence. The thickness is about 250μm to 450μm (see Figure 2 The paint stripper of Example 5 was evenly applied on the paint surface of the paint board, left to stand for 50 minutes, and washed with water. It can be seen that the paint film has bubbled and can be easily lifted by hand and completely separated from the bottom plate, as shown in FIG. Figure 3 shown.
Claims
1. A modified hydrotalcite prepared by the following steps: I. Using Zn(NO3)26H2O, A1(NO3)39H2O and hexamethylenetetramethyltetramine (HMT) as raw materials, hydrotalcite with an average particle size of 2.0 to 3.0 μm was obtained by hydrothermal reaction; II. The hydrotalcite obtained in step I is added to a Tris-HCl-NaCl buffer solution of polyaspartic acid, ultrasonically dispersed for 10 to 30 minutes, and then magnetically stirred for 20 to 60 minutes; liquid-solid separation, the obtained solid is rinsed with distilled water at least 3 times, and dried to obtain; The mass ratio of polyaspartic acid to the hydrotalcite is 1:5-20.
2. The modified hydrotalcite according to claim 1, characterized in that: In step I, the molar ratio of Zn(NO3)26H2O, Al(NO3)39H2O and hexamethylenetetramethyltetramine is: Zn(NO3)26H2O∶A1(NO3)39H2O∶hexamethylenetetramethyltetramine=2:1~1.5:4; Preferably, in step I, the hydrothermal reaction temperature is 130-180° C., and the reaction time is 10-18 hours; Preferably, the hydrotalcite is prepared by the following steps: I-1. Add Zn(NO3)26H2O and A1(NO3)39H2O to water at 50-70°C to a concentration of 0.05-0.15 mol / L of zinc nitrate; then add hexamethylenetetramethyltetramine and stir thoroughly to dissolve; wherein the molar ratio of Zn(NO3)26H2O, A1(NO3)39H2O and hexamethylenetetramethyltetramine is: Zn(NO3)26H2O∶A1(NO3)39H2O∶hexamethylenetetramethyltetramine=2:1:4; I-2. The mixed solution obtained in step I-1 was transferred to a hydrothermal reactor, heated to 130 to 180 ° C, kept for 10 to 18 hours, and cooled to room temperature; I-3. The reaction system obtained in step I-2 was centrifuged, and the precipitate was washed with water at least 3 times, 30 to 50 ml each time; then washed with 98% ethanol at least 3 times, 30 to 50 ml each time; dried at 60 to 70 ° C for 8 to 12 hours, ground into a fine powder, and passed through a 120 to 150 mesh sieve to obtain; Preferably, in step I-1, the concentration of zinc nitrate is 0.1 mol / L; Preferably, in step I-2, the temperature of the hydrothermal reaction is 140 to 160° C., more preferably 150° C.; the hydrothermal reaction time is 12 to 16 hours, more preferably 14 hours; Also preferably, in the step I-2, the hydrothermal reaction kettle can be transferred to a heating device for heating to perform a hydrothermal reaction; More preferably, the heating device is an oven; Preferably, in step I-3, the drying temperature is 65° C. and the drying time is 10 h; Also preferably, in step I-3, drying is carried out in a forced air drying oven.
3. The modified hydrotalcite according to claim 1, characterized in that: In step II, the concentration of polyaspartic acid in Tris-HCl-NaCl buffer was 1 mg / ml; Preferably, the Tris-HCl-NaCl buffer is prepared by the following method: Take Tris base and NaCl and dissolve them in distilled water to make the concentration of Tris base 0.6-0.7 mol / L, and adjust the pH value to 8.5-9 with dilute hydrochloric acid to obtain the product; wherein the molar ratio of Tris base to NaCl is 1:3; Preferably, in step II, the ultrasonic dispersion time is 15 to 25 min, more preferably 20 min; Preferably, in step II, the magnetic stirring time is 25 to 35 min, more preferably 30 min; Also preferably, in step II, the drying is vacuum drying, the drying temperature is 50 to 70° C., and the drying time is 12 to 24 hours.
4. A composition comprising the modified hydrotalcite according to any one of claims 1 to 3, and further comprising a main solvent, D-limonene, dimethyl succinate, triethanolamine, a surfactant, bio-glue, benzotriazole and water; based on the total mass of the composition, the mass percentage of each component is: The modified hydrotalcite comprises 0.5-2%, the main solvent comprises 30-40%, D-limonene comprises 5-10%, dimethyl succinate comprises 5-10%, triethanolamine comprises 4-8%, a surfactant comprises 0.05-0.5%, biological glue comprises 1-5%, benzotriazole comprises 0.1-1%, and the balance comprises water; in, The main solvent is selected from one or more of ethylene glycol monoethyl ether, benzyl alcohol, cyclohexanol and heptanol in any proportion; The surfactant includes a nonionic surfactant and an anionic surfactant.
5. The composition according to claim 4, characterized in that The mass percentages of the components of the composition are: The modified hydrotalcite comprises 0.8-1.6%, the main solvent comprises 30-38%, D-limonene comprises 5-10%, dimethyl succinate comprises 5-10%, triethanolamine comprises 4-8%, a surfactant comprises 0.05-0.5%, biological glue comprises 1-5%, benzotriazole comprises 0.1-1%, and the balance comprises water; More preferably, the mass percentages of the components of the composition are: The modified hydrotalcite comprises 1-1.5%, the main solvent comprises 35-37%, D-limonene comprises 6-7%, dimethyl succinate comprises 6-7%, triethanolamine comprises 5-6%, surfactant comprises 0.2-0.3%, biological glue comprises 1.5-2%, benzotriazole comprises 0.5-0.7%, and the balance comprises water.
6. The composition according to claim 4 or 5, characterized in that The nonionic surfactant is selected from one or more of alkylphenol polyoxyethylene ethers, alkylolamides and alkyl glycosides with an n value greater than 8; Preferably, the anionic surfactant is sodium dodecylbenzene sulfonate; Preferably, the mass ratio of the nonionic surfactant to the anionic surfactant is 1:1 to 3:1; Preferably, the bio-gum is selected from one or more of tri-gum, xanthan gum and guar gum in any proportion.
7. A paint stripper, using the composition according to any one of claims 4 to 6 as a raw material.
8. The method for preparing the paint stripper according to claim 7, comprising the steps of: A. Prepare the components according to the ratio; B. The main solvent and D-limonene are mixed uniformly in a container, and triethanolamine, a surfactant and the modified hydrotalcite are added and mixed uniformly to obtain a mixed solution A for standby use; C. Mix water, dimethyl succinate, bio-glue and benzotriazole in a container to obtain a mixed solution B for later use; D. Mix the mixed solution A obtained in step B and the mixed solution B obtained in step C, and stir them evenly to obtain the product.
9. Use of the paint stripper according to claim 7 or the paint stripper obtained by the preparation method according to claim 8 in paint removal, especially in paint removal on the surface of EMU body.
10. A paint stripping process, comprising using the paint stripper according to claim 7 or the paint stripper obtained by the preparation method according to claim 8, comprising the following steps: The paint stripper according to claim 7 or the paint stripper obtained by the preparation method according to claim 8 is directly applied on the paint surface to be stripped, left to stand for 40 minutes to 1 hour, then the bulging paint film is peeled off, the paint stripping residue is cleaned, and the paint stripper is rinsed with water; Preferably, the paint surface to be removed includes the paint layer applied on the surface of the EMU train body.
Citation Information
Patent Citations
Polyaspartic acid intercalated hydrotalcite composite material, preparation method and application thereof
CN110624513A
Paint remover, paint removing method and application of paint remover
CN117701058A
Paint remover composition and preparation method thereof
CN117859121A
Water-based paint remover and preparation method thereof
CN118085631A
Cited By
Controllable-release solid corrosion and scale inhibitor and preparation method thereof
CN119841469A